Network Learning: Interinstitutional cooperation in the performance of the International Climate Resilience Research Network – RIPEDRC (Research, Society and Development, 2021)
This paper is a result of the Postdoctoral research project at the Post graduation Program in Education at Federal University of Mato Grosso, Brazil, which integrates teaching, research and extension. It has been developed in several Brazilian cities, regions and states as well as in thirteen countries. An interdisciplinary research was developed with some researchers from the “International Research Network Climate Resilience - RIPEDRC”. The study was developed in three phases: the first one presents a context of the environmental crisis and its interfaces with climate emergency and climate justice. The nowadays periods are highlighted by deep changes in all fields of knowledge and human life. Therefore, the socio-ecological and human crisis settle on the planet, presented in this study have been recognized by Loureiro (2004), Leff (2006), Wilson (2008), Carniatto (2007), Lovelock (2010), Boff (2012), Zohar & Marshall (2012), Carniatto; Rosa & Oliveira, (2015), Serantes-Pazos & Meira-Cartea (2016), Pereira & Amaral (2020), and by Foster (2020). The second one shows the methodological path according to the action-research and, finally, presents results based on the participants’ narratives, the meaning, scope, and cooperation potential in RIPEDRC by researchers who are members of this network. The results suggest scenarios such as great carelessness with life, vulnerable social groups and socially excluded people. So, RIPEDRC aims at addressing climate emergencies and climate justice at the community. The answers point for a significant importance of this network organization both for the environmental field and coping the main issues associated to the climate in a cooperative and collective dynamic.